Phenotypic plasticity and growth temperature: understanding interspecific variability - Atkin, O. K; Loveys, B. R; Atkinson, L. J; Pons, T. L (Journal of experimental botany, 2006)
The subject of this review is the impact of long-term changes in temperature on plant growth and its underlying components. The discussion highlights the extent to which thermal acclimation of metabolism is intrinsically linked to the plasticity of a range of biochemical and morphological traits. The fact that there is often a trade-off between temperature-mediated changes in net assimilation rates (NAR) and biomass allocation [in particular the specific leaf area (SLA)] when plants are grown at different temperatures is also highlighted. Also discussed is the role of temperature-mediated changes in photosynthesis and respiration in determining NAR values. It is shown that in comparisons that do not take phylogeny into account, fast-growing species exhibit greater temperature-dependent changes in RGR, SLA, and NAR than slow-growing plants. For RGR and NAR, such trends are maintained within phylogenetically independent contrasts (i.e. species adapted to more-favourable habitats consistently exhibit greater temperature-mediated changes than their congeneric counterparts adapted to less-favourable habitats). By contrast, SLA was not consistently more thermally plastic in species from favourable habitats. Interestingly, biomass allocation between leaves and roots was consistently more plastic in slow-growing species within individual phylogenetically independent contrasts, when plants were grown under contrasting temperatures. Finally, how interspecific variations in NAR account for an increasing proportion of variability in RGR as growth temperatures decrease is highlighted. Conversely, SLA played a more dominant role in determining interspecific variability in RGR at higher growth temperatures; thus, the importance of SLA in determining interspecific variation in RGR could potentially increase if annual mean temperatures increase in the future.